Toxicity of Atenolol and Propranolol on Rat Heart Mitochondria - Seydi, Enayatollah; Tabbati, Yasaman; Pourahmad, Jalal (Drug Research, 2020)
Propranolol and atenolol are known as β receptor blocker drugs. These drugs are used to treat some heart diseases. There are controversies in the relationship between the use of beta-blocker drugs and the level of reactive oxygen species (ROS). Mitochondria as one of the most important sources of ROS are considered as one of the targets of drug-induced cardiotoxicity. The aim of this study was to evaluate the effects of propranolol and atenolol on mitochondria isolated from the heart. To achieve this aim, several markers of mitochondrial and cellular toxicity were evaluated. The key results of this study are the increased ROS level, collapse in mitochondrial membrane potential (MMP), mitochondrial swelling and cytochrome c release as well as disruption of respiratory chain complex II in mitochondria in isolated heart mitochondria after exposure to propranolol and atenolol. The results indicate an increase in caspase-3 activity and a decrease in the ATP level in cardiomyocytes after exposure to propranolol and atenolol. The underlying mechanisms of propranolol and atenolol induced cardiotoxicity may be associated with alterations in mitochondrial function, oxidative stress, and changes in the mitochondrial membrane.
Keywords: propranolol; atenolol; heart mitochondria; reactive oxygen species.